Radiodensitometric and DXA analyses for the measurement of bone mineral density after systemic alendronate therapy - Marília Pacífico Lucisano; Paulo Nelson-Filho; Leslie Morse; Ricardo Battaglino; Plauto Christopher Aranha Watanabe; Raquel Assed Bezerra da Silva; Lea Assed Bezerra da Silva (Sociedade Brasileira de Pesquisa Odontológica, 2013)
Precise techniques for the measurement of maxillary bone mineral density (BMD) are useful for the early diagnosis of systemic diseases. The aim of this study was to compare in vivo the efficacy of dual-energy x-ray absorptiometry (DXA) and radiographic densitometry for the measurement of BMD after systemic administration of sodium alendronate. Wistar rats were randomly allocated to a control group (n = 5), which received distilled water, and a sodium alendronate group (n = 8), which received two doses of chemically pure sodium alendronate (1 mg/kg) per week. After 8 weeks, the animals were euthanized, the tibias were removed, and the BMD of the proximal tibial metaphysis was analyzed radiographically and by DXA. The data were subjected to statistical analysis by the Kruskal-Wallis test at a significance level of 5%. Both of the techniques revealed that the alendronate-treated group had a significantly higher BMD (p < 0.05) than the control group after 8 weeks of treatment. Comparing the groups with and without alendronate therapy revealed increases of 14.9% and 29.6% in BMD, as detected radiographically and by DXA, respectively. In conclusion, both of the methods were able to detect an increase in BMD of the proximal tibial metaphysis after alendronate therapy.